Synthesis, Characterization, Antifungal and Antibacterial Activity of Mixed Ligand Complexes of Cu(II), Ni(II) and Co(II) - Sharma, Munesh; Singh, Dharmendra; Kumar, Rakesh; Lata, Suman; Singh, Vijendra (Asian Journal of Chemistry, 2010)
Metal complexes of the type ML1L2 [M = Cu(II), Ni(II) and Co(II), L1 = 3,3'-dipyridyl(dipy.), L2 = 2-hydroxybenzalidine anthranilic acid (HBAA)] have been synthesized by using 3,3'- dipyridyl(dipy.), 2-hydroxybenzalidine anthranilic acid (HBAA) and metal(II) acetate. The resulting mixed ligand metal complexes have been characterized on the basis of elemental analysis, IR-spectra, electronic spectra, magnetic susceptibilities and molar conductance measurements. The antifungal and antibacterial activities of ligands and there metal complexes have been screened against Aspergillus flavus, Aspergillus fumigatus, Aspergillus niger, Escherichia coli and Staphylococcus aureus.